Human Platelet-Rich Plasma Facilitates Angiogenesis to Restore Impaired Uterine Environments with Asherman’s Syndrome for Embryo Implantation and Following Pregnancy in Mice - Min Kyoung Kim; Jung Ah Yoon; Sook Young Yoon; Mira Park; Woo Sik Lee; Sang Woo Lyu; Haengseok Song (Cells, 2022)
Asherman’s syndrome (AS) is caused by intrauterine adhesions and inactive endometrium from repeated curettage of the uterine endometrium. AS is a major cause of recurrent implantation failure and miscarriage and is very difficult to treat because of the poor recovery of endometrial basal cells. Platelet-rich plasma (PRP) has abundant growth factors that may induce angiogenesis and cell proliferation. Here, we demonstrate that human PRP (hPRP) significantly enhances angiogenesis to restore embryo implantation, leading to successful pregnancy in mice with AS. In mice with AS, hPRP treatment considerably reduced the expression of fibrosis markers and alleviated oligo/amenorrhea phenotypes. Mice with AS did not produce any pups, but the hPRP therapy restored their infertility. AS-induced abnormalities, such as aberrantly delayed embryo implantation and intrauterine growth retardation, were considerably eliminated by hPRP. Furthermore, hPRP significantly promoted not only the elevation of various angiogenic factors, but also the migration of endometrial stromal cells. It also increased the phosphorylation of STAT3, a critical mediator of wound healing, and the expression of tissue remodeling genes in a fibrotic uterus. PRP could be a promising therapeutic strategy to promote angiogenesis and reduce fibrosis in impaired uterine environments, leading to successful embryo implantation for better clinical outcomes in patients with AS.